2015
DOI: 10.1371/journal.pone.0126060
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting GMOs: Are There Differences in European Consumers’ Acceptance and Valuation for Cisgenically vs Transgenically Bred Rice?

Abstract: Both cisgenesis and transgenesis are plant breeding techniques that can be used to introduce new genes into plant genomes. However, transgenesis uses gene(s) from a non-plant organism or from a donor plant that is sexually incompatible with the recipient plant while cisgenesis involves the introduction of gene(s) from a crossable—sexually compatible—plant. Traditional breeding techniques could possibly achieve the same results as those from cisgenesis, but would require a much larger timeframe. Cisgenesis allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 22 publications
12
98
0
Order By: Relevance
“…This result shows that consumers are willing to pay US$13.75 more per 5kg bag, a premium of 275%, for a rice variety that was produced with no fungicide. These findings are consistent with those found in similar studies by Delwaide et al (2015) and Shew et al (2016) in the European Union and India, respectively. Their research, which was also hypothetical, shows that consumers in France and India are willing to pay a premium of 667% and 486%, respectively for rice that is labeled, EB, as compared to conventional rice.…”
Section: Interval Regression Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This result shows that consumers are willing to pay US$13.75 more per 5kg bag, a premium of 275%, for a rice variety that was produced with no fungicide. These findings are consistent with those found in similar studies by Delwaide et al (2015) and Shew et al (2016) in the European Union and India, respectively. Their research, which was also hypothetical, shows that consumers in France and India are willing to pay a premium of 667% and 486%, respectively for rice that is labeled, EB, as compared to conventional rice.…”
Section: Interval Regression Resultssupporting
confidence: 93%
“…They also perceived CIS rice to be different (P<0.05) from GM rice, but not different from transgenic rice. These findings are similar to the results from Delwaide et al (2015) which indicated that there are significant differences across countries in terms of the attitudes towards CIS and transgenic rice. Such findings imply that consumers differentiate between CIS and transgenic products and tend to have a less negative attitude towards CIS rice than towards transgenic rice.…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
See 1 more Smart Citation
“…Although no scientific evidence has been related so far to a safer use of cisgenesis instead of transgenesis, a more positive consumers' perception has been reported towards the use of genes from a compatible gene pool [80][81][82]. Clearly, it adds a new dimension to the debate on GMO [83].…”
Section: Cisgenic Potatoes In Organic Farming: Scientific Legislativmentioning
confidence: 99%
“…Nowadays more than 15 states in the United States are considering such legislation of food labeling 29 . A study conducted with 3002 participants in Belgium, France, the Netherland, Spain and the United Kingdom found that consumers are willing to pay a premium to avoid purchasing rice labeled as genetically modified 30 . In a study of medical students, 84.9% of them stated that if a food is genetically modified, this should be indicated on the label.…”
Section: Results:-mentioning
confidence: 99%